Effectiveness of awareness raising interventions on knowledge about Rheumatic Heart Disease and change in care seeking behavior for throat infection in Lalitpur, Nepal - Regmi, Prakash Raj; Sanjel, Keshab (Nepalese Heart Journal, 2019)
Background and Aims: Awareness raising is an important component of primary prevention of RHD. Data are lacking on primary prevention activities for rheumatic heart disease (RHD) prevention in Nepal. The aim of this study is to assess the effectiveness of various awareness raising activities on increasing knowledge about throat infection (TI), acute rheumatic fever (ARF) and RHD and their impact on RHD prevention. Methods: Fourteen randomly selected government health facilities in Lalitpur were enrolled in this study. A baseline study conducted in early 2015 analyzed the level of knowledge about RHD among care seekers attending health facilities in Lalitpur. An expansive public awareness raising activities on RHD were performed for 2.5 years starting from February 2015. Data were collected using structured interviews, and review of health facility records. Data were analyzed to compare the postintervention status with the baseline status. Results: The mean knowledge about ARF and RHD increased by over 71% (1.82 to 3.12) and 124% (0.37 to 0.83) respectively in post intervention group. There was significant difference in knowledge about TI, ARF and RHD among baseline and post intervention group (p-value<0.0001). The number of throat infection cases presented at health facilities increased by 30.39% from fiscal year (FY) 2071/72 to FY 2072/073 and by 4.69% in the next FY. Conclusions: Awareness raising interventions are effective in increasing knowledge about TI, ARF and RHD which further can produce positive impact in the primary prevention of ARF and RHD.